Kutatói feladat adatgyűjtésének internetes támogatása - Orova, Lászlóné (Acta Agraria Kaposváriensis, 2006)
Data collection is an important part of the research in all disciplines. In technical research measurements data coming from testing equipments are stored digitally to avoid additional errors coming from data recording and reduce data entering resources. In other disciplines like marketing research data collection is not supported by instruments. New tools are provided for collection of personal opinion by the widely spreading Internet. My research is the investigation of new product diffusion process in Hungary. It is inconceivable without asking the opinion of the market players. To facilitate the data collecting procedure, I have made e-mail and Web-based questionnaire surveys. The aim of this work is presenting the experiences in this methods and comparing the results with the international findings. The survey by e-mail presented quick and exact data. The Web-based questionnaire with its non linear structure has facilitated the filling in and the data recording. It made possible to follow up the filling in procedure as well. The rate of the lurker and answering drop-outs differs from previous results of Bosnjak. Citizens filled in the mayor part of the questionnaires and the personal contact proved is advantageous to the care of filling out.
Keywords: data collection; questionnaire; Internet; WEB-programming